How to Managing Emotion and Mood of Work Patterns From Home On The Performance Of Employees of Private Universities In South Kalimantan? - Wahyu Artiningsih, Dwi; Muthia, Harnida; Zamilah, Ervica; Rizka Zulfikar (Publisher Cv. Inara, 2021)
Facing the condition of COVID-19, of course, it greatly affects the psychological and mental condition of a person who tends to be more emotional in responding to something because of the stress of the situation and the various demands that must be lived. One example is the Work From Home pattern where it can trigger emotions and affect the mood of employees. The purpose of this study: 1) analyzing emotions significantly affect employee performance, 2) analyzing work mood has a significant effect on employee performance, 3) analyzing work emotions and moods has a significant effect on employee performance. This research was an explanatory research with quantitative approach (positivism). The population of this study was private universities in South Kalimantan education staff with a total sample of 252 respondents and these samples was taken by purposive sampling techniques. Data analysis was using Multiple linear regression. The results showed; 1) emotions have a significant effect on employee performance, 2)work mood has a significant impact on employee performance, 3) emotions and work mood have a significant impact on employee performance. The findings in this study that emotions and working mood when managed well will greatly impact employee performance. The existence of work from home policy, employees' emotions and work mood are sometimes disturbed by various activities that change, such as all activities carried out at home and there needs to be conformity with the home environment that tends to be no more conducive than at work.